Odpowiedzi

Najlepsza Odpowiedź!
2009-10-18T20:46:54+02:00
W=(2x - y)³ - (2x - y)² - (4x - 3y) (4x + 3y) + 12xy + y³ + 20x² + 4xy=
=8x³-6x²y+6xy²-y³-16x²+9y²+ 12xy + y³ + 20x² + 4xy=
=8x³-6x²y+6xy²+4x²+9y²+16xy
8√5³-6√5²2√5+6√5(2√5)²+4√5²+9(2√5)²+16√5*2√5=
=40√5-60√5+120√5+20+180+160=
=100√5+360
2009-10-18T21:49:37+02:00
W=8x^3 -y^3 -4x^2 - y^2 - (16x^2 +12xy -12xy -9y^2) +12x^2y +y^3 + 20x^2 +4xy
W=8x^3-y^3-4x^2-y^2-16x^2+9y^2+12x^2y+y^3+20x^2+4xy
W=8x^3+8y^2+12x^2y+4xy

X=√5
Y=-2√5
W=8(√5)^3+8(2√5)^2+12[(√5)^2*2√5]+4(√5*2√5)
W=40√5+160+12[5*2√5]+4(10)
W=40√5+160+120√5+40
W=160√5+200

:)